How Will I Evaluate Others? The Influence of “Versailles Literature” Language Style on Social Media on Consumer Attitudes Towards Evaluating Green Consumption Behavior - Huilong Zhang; Huiming Liu; Yudong Zhang; Hui He (Behavioral Sciences, 2025)
The dissemination and practice of green consumption behavior is an important issue in promoting sustainable development. With the advent of the digital age, social media platforms have become an important channel for promoting green consumption. The expression of language style has become an increasingly important factor influencing consumer attitudes. From the perspective of consumer perception, this study used three situational simulation experiments (n total = 304) to explore the mechanism by which the “Versailles Literature” language style impacts the feelings and behaviors of audiences of the green consumption behavior of the poster, and to examine the mediating roles of ostentation perception and hypocrisy perception. Data analysis was conducted using SPSS. The research findings showed that, compared with “non-Versailles Literature”, this style significantly reduces positive attitudes toward green consumption while increasing perceptions of bragging and hypocrisy. Furthermore, the strength of social ties between the consumer and the poster plays a moderating role in the effect of language style; specifically, when posts come from strangers, consumers perceive a stronger sense of bragging and hypocrisy. The research results will provide practical guidance for individuals and enterprises to effectively promote the concept of green consumption on social media, helping enterprises avoid the negative reactions brought about by conspicuous green consumption behaviors and exaggerated or false promotion of environmental behaviors, such as “greenwashing”.